Absence of the glycosyltransferase WcaJ in Klebsiella pneumoniae ATCC13883 affects biofilm formation, increases polymyxin resistance and reduces murine macrophage activation. Issue 8 (27th June 2019) - Pal, Shilpa; Verma, Jyoti; Mallick, Sathi; Rastogi, Sumit Kumar; Kumar, Akash; Ghosh, Anindya S.
Abstract : Multidrug-resistant Klebsiella pneumoniae has emerged as one of the deadliest opportunistic nosocomial pathogens that forms biofilm for the establishment of chronic K. pneumoniae infections. Herein, we made an attempt to identify the genes involved in biofilm formation in the strain K. pneumoniae ATCC13883. To achieve this, we constructed mini-Tn5 transposon insertion mutants and screened them for biofilm production. We observed that the biofilm formation was enhanced in the mutant where the wcaJ gene was disrupted. WcaJ is the initiating enzyme of colanic acid synthesis and loads the first sugar (glucose-1-P) on the lipid carrier undecaprenyl phosphate. The absence of this glycosyltransferase results in the absence of colanic acid, which renders a non-mucoid phenotype to the mutant. Further, to determine the effect of mucoidy on antibiotic susceptibility, we tested the sensitivity of the strains towards different groups of antibiotics. Unlike the mucoid strains, the resistance of the non-mucoid cells was greater for polymyxins, but less for quinolones. Capsular polysaccharides are known to have a protective effect against phagocytosis, therefore we assessed the role of colanic acid in virulence by conducting infection studies on murine macrophages. Surprisingly, the Δ wcaJ strain was less efficient in macrophage activation and was not readily phagocytosed. Thus, the presence of colanic acid appeared to increase the immunogenicity of K. pneumoniae . Overall, the results indicate that the presence of colanic acid increases the vulnerability of K. pneumoniae towards both polymyxins and macrophages, implying that the mucoid strains are less threatening as compared to their high biofilm forming non-mucoid counterparts.